The persian version of mhealth app usability questionnaire (MAUQ) for patients: a psychometric assessment study - Khadijeh Moulaei; Fatemeh Dinari; Abbas Sheikhtaheri; Kambiz Bahaadinbeigy; Sadrieh Hajesmaeel-Gohari (BMC Medical Informatics and Decision Making)
Abstract Introduction The growing importance of mobile apps in osteoporosis management highlights the crucial need for evaluating their utility and usability, particularly for Osteoporosis support apps. Addressing this need, the mHealth App Usability Questionnaire (MAUQ) was crafted in four different versions, categorized based on the nature of the app (interactive or standalone) and the intended user (patient or provider). Due to its usage by diverse users with varying languages, this questionnaire requires psychometric assessment in multiple languages. This study aimed to translate and validate the Persian version of MAUQ for patients. Method After translating the standalone and interactive versions of MAUQ into the Persian language, face validity, content validity, and factor analysis were conducted. Ten patients with osteoporosis were involved for face validity, and ten experts in medical informatics and health information technology were invited to assess content validity by completing a questionnaire. A total of 99 patients with osteoporosis participated in the factor analysis. The reliability of the questionnaires was assessed by calculating Cronbach’s alpha. Results The face validity and the content of the Persian version of MAUQ were confirmed. Factor analysis of the standalone version of MAUQ showed 18 items in three dimensions: easy to use (7 items), user interface and satisfaction (6 items), and usefulness (5 items). Factor analysis of the interactive version of MAUQ showed 21 items in two dimensions: easy to use and satisfaction (11 items) and information arrangement and usefulness (10 items). The Cronbach’s alpha of the questionnaire for standalone and interactive applications was 0.90. Conclusion The psychometric assessment of the Persian MAUQ established its validity and reliability among osteoporosis patients, affirming its efficacy as a robust tool for evaluating mHealth app usability.